2017
DOI: 10.2147/jep.s133778
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic activity of the aqueous crude extract and hot tea infusion of <em>Moringa stenopetala </em>(Baker f.) Cufod. leaves in rats

Abstract: Moringa stenopetala (Baker f.) Cufod. is a medicinal plant that has been used for the treatment of different ailments such as hypertension and diabetes in Ethiopia. This study aims to assess the diuretic activity of the aqueous crude extract and hot tea infusion of M. stenopetala leaves in saline-loaded rats. Male Wistar rats were divided into ten groups (n = 5). The control group received distilled water (5 mL/kg), whereas the reference group received Furosemide (10 mg/kg). Groups III–X orally received differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 20 publications
(27 reference statements)
4
37
0
2
Order By: Relevance
“…In the mice given the EO, at the two doses, the ionic quotient is not between 0.8 and 1 as in the control mice. It is reported that substances that do not cause the ionic quotient between 0.8 and 1 inhibit carbonic anhydrase (Netsanet et al, 2017). However, the inhibition of carbonic anhydrase leads to the inhibition of the concomitant reabsorption of bicarbonates, sodium and chlorine, at the level of the proximal tubule.…”
Section: Discussionmentioning
confidence: 99%
“…In the mice given the EO, at the two doses, the ionic quotient is not between 0.8 and 1 as in the control mice. It is reported that substances that do not cause the ionic quotient between 0.8 and 1 inhibit carbonic anhydrase (Netsanet et al, 2017). However, the inhibition of carbonic anhydrase leads to the inhibition of the concomitant reabsorption of bicarbonates, sodium and chlorine, at the level of the proximal tubule.…”
Section: Discussionmentioning
confidence: 99%
“…4-(R-L-rhamnopyranosyloxy)-benzylglucosinolate: 59.4±1.4 mg/g DW in young leaves and 33.9±0.9 4 mg/g DW in old leaves). Mekonnen and Drager (2003) Fekadu et al, 2017;Geleta et al, 2016b). Toma et al (2014) and Melesse et al (2017) also reported the presence of condensed tannins in either ethanol extracts or dried leaves of M. stenopetala (i.e.…”
Section: Glucosinolates and Isothiocyanatesmentioning
confidence: 94%
“…Moringa leaf aqueous and hot tea extracts significantly increased UV, UNa + , UK + , and UCl − excretion compared with the control group. 15…”
Section: Moringamentioning
confidence: 99%
“…A growing body of evidence, including several animal studies reported in the present systematic review, has refined and extended the concept of a diuretic index to more objectively appraise diuretic activity. [11][12][13][14][15][16][17] Specifically, the diuretic index is defined as ratio of urine excretion in a test group to a control group, wherein substances with a diuretic index >1.5, between 1-1.5, 0.72-1, and <0.72 have been described as having "good," "moderate," "mild," and "minimal/absent" diuretic activity, respectively. 15 Based on this assessment, food items such as wild raspberry, 12 goji berries, 13 moringa, 15 black cumin, 17 and Tulkarm honey 11 have shown good diuretic activity in animal studies.…”
Section: Implementation and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation